Apoyo a la productividad de los pobres rurales: nuevas experiencias en América Latina y el Caribe = Support for the productivity of the rural poor: new experiences in Latin America and the Caribbean - NU. CEPAL (CEPAL, 2014)
Incluye Bibliografía